Asymmetry in exchange rate pass-through to consumer prices: New perspective from sub-Saharan African countries - Diby François Kassi; Dilesha Nawadali Rathnayake; Akadje Jean Roland Edjoukou; Yobouet Thierry Gnangoin; Pierre Axel Louembe; Ning Ding; Gang Sun (Economies, 2019)
This paper examines the asymmetrical relationship between exchange rate and consumer prices in 40 sub-Saharan African (SSA) countries from 1990Q1 to 2017Q4. We estimate the exchange rate pass-through (ERPT) to consumer prices for each country by using the nonlinear autoregressive distributed lag (NARDL) framework and dynamic panel techniques robust to cross-sectional dependence. First, our findings suggest an asymmetrical ERPT in the SSA region during the short term, whereas there are mixed results across subregions in the long term. Second, the results of the panel analysis suggest incomplete and significant ERPT to consumer prices in the entire SSA region, which is higher during depreciation of the local currency than after appreciation in the short-term, especially in the CFA Franc zone. Third, we find nonlinear ERPT with respect to the size of the exchange rate. Finally, we find that pass-through is higher in countries with fixed exchange rate regimes (CFA franc zone) in a low inflationary environment than in countries with floating exchange rate regimes and high inflation levels. Pass-through is greater during large exchange rate changes than after small changes. Therefore, the policy implication is to consider these asymmetries and nonlinearities to improve monetary policy's credibility, enhance trade liberalization, and promote competitive market structures in the SSA region.
Keywords: 330; asymmetry; exchange rate pass-through; NARDL; inflation; sub-Saharan Africa